Analysis of Factors Associated with Utilization of Posyandu Elderly Health Services - Sulastri, Norjainah; Adhani, Rosihan; Shadiqi, Muhammad Abdan; Ringoringo, Harapan Parlindungan; Febriana, Silvia Kristanti Tri (Newinera Publisher, 2024)
Puskesmas Panarung is the coverage of elderly health services with the lowest utilization of 559 elderly (25.0%) data on the number of elderly visits from both the Health Office and the health center has not reached the target of 70%. To determine the relationship between motivation, family support, accessibility, and service quality with the utilization of oral health services at the Panarung City Health Center. This study used a cross sectional design. The study subjects consisted of 94 people at the Panarung City Health Center. Data analysis chi square test and multiple logistic regression test. The results of the analysis is the most dominant variables related to the Utilization of Posyandu Elderly Health Care Services in the working area of Puskesmas Panarung are motivation (17.767), family support (15.046), service quality (10.797), and accessibility (7.956). There is a relationship between motivation, family support, accessibility, and service quality with the utilization of posyandu health services for the elderly. The most dominant variable is motivation.